Passenger satisfaction with cleanliness and other service quality dimensions and gender as a moderator: Evidence from Indian Railways - Magheswari Gopal Vasanthi; Vasanthi Soundrarajan; Nishad Nawaz; Vijayakumar Gajendran; Satyanarayana Parayitam (Cogent Business & Management, 2023)
The present study's objective is to examine the customer satisfaction on cleanliness and other service quality dimensions in Indian Railways. In addition, gender as a moderator in the relationship between various service quality dimensions and passenger satisfaction is studied. The data was collected from 544 passengers in the Tiruchirappalli railway station (Southern Railway Zone). The data was collected between September 2021 and December 2021, soon after the restoration of services after the global pandemic. Data was collected while taking precautions of social distancing and by wearing facemasks. A structured instrument SERVQUAL was used, and the results indicate that passengers were satisfied with the tangibility, assurance, and reliability dimensions of service quality. We performed regressions showing the relationship between service quality variables and passenger satisfaction. We also studied gender as a moderator in the relationship between the five service quality dimensions and passenger satisfaction. The results indicate that gender moderates the relationship between tangibility and customer satisfaction and reliability and passenger satisfaction. The implications for management are discussed.
Keywords: 650; gender; passenger satisfaction; SERVQUAL Indian Railways